Temperature Regimes Impact Coral Assemblages along Environmental Gradients on Lagoonal Reefs in Belize. - Justin H Baumann (PLoS ONE, 2016)
Coral reefs are increasingly threatened by global and local anthropogenic stressors such as rising seawater temperature, nutrient enrichment, sedimentation, and overfishing. Although many studies have investigated the impacts of local and global stressors on coral reefs, we still do not fully understand how these stressors influence coral community structure, particularly across environmental gradients on a reef system. Here, we investigate coral community composition across three different temperature and productivity regimes along a nearshore-offshore gradient on lagoonal reefs of the Belize Mesoamerican Barrier Reef System (MBRS). A novel metric was developed using ultra-high-resolution satellite-derived estimates of sea surface temperatures (SST) to classify reefs as exposed to low (lowTP), moderate (modTP), or high (highTP) temperature parameters over 10 years (2003 to 2012). Coral species richness, abundance, diversity, density, and percent cover were lower at highTP sites relative to lowTP and modTP sites, but these coral community traits did not differ significantly between lowTP and modTP sites. Analysis of coral life history strategies revealed that highTP sites were dominated by hardy stress-tolerant and fast-growing weedy coral species, while lowTP and modTP sites consisted of competitive, generalist, weedy, and stress-tolerant coral species. Satellite-derived estimates of Chlorophyll-a (chl-a) were obtained for 13-years (2003-2015) as a proxy for primary production. Chl-a concentrations were highest at highTP sites, medial at modTP sites, and lowest at lowTP sites. Notably, thermal parameters correlated better with coral community traits between site types than productivity, suggesting that temperature (specifically number of days above the thermal bleaching threshold) played a greater role in defining coral community structure than productivity on the MBRS. Dominance of weedy and stress-tolerant genera at highTP sites suggests that corals utilizing these two life history strategies may be better suited to cope with warmer oceans and thus may warrant protective status under climate change.